Brazilian front-of-package nutrition labeling: consumer perceptions on social media platform X - Ribeiro, Mariana; Matos, Juliana de Paula; Kikuta, Carolina; Marques, Thais da Silva; Arruda, Beatriz Escaler; Horta, Paula Martins; Martins, Ana Paula Bortoletto; Mais, Laís Amaral (Frontiers in Nutrition, 2025)
ObjectiveThis study aimed to analyze how the Brazilian front-of-package nutrition labeling (FOPNL) policy has been represented and discussed on the social media platform X (formerly Twitter).MethodsA cross-sectional observational study was conducted based on 2,323 posts published by personal user accounts on X between October 2020 and April 2024. All posts were written in Portuguese and contained terms related to Brazilian FOPNL. The posts analysis comprised: (i) publication type (science, information, opinion, regulation), (ii) positioning on FOPNL (positive, moderately positive, neutral, moderately negative, negative), and (iii) thematic content, based on eight thematic categories: nutrients of concern, health risk, regulatory aspects, no effect, support for the regulation, critiques and concerns, decision-making and others. Descriptive statistics were used to examine the distribution of posts over time and the relationship between thematic categories and positions on FOPNL.ResultsThe number of posts increased progressively over the study period. The most prevalent thematic categories were nutrients of concern (92.0% CI 95% 90.86–93.07), critiques and concerns (31.2% CI 95% 29.40–33.17) and no effect (29.8% CI 95% 28.00–31.73). Favorable perceptions on FOPNL were noted, particularly in posts supporting the regulation (67.36%), whereas negative positions were more commonly found in the “critiques and concerns” category (91.36%). Thematic analysis revealed a variety of user reactions, including expressions of surprise, discomfort, or dissatisfaction, often conveyed through ironic or sarcastic tones.ConclusionThe implementation of FOPNL in Brazil was accompanied by increasing public engagement over time. It was possible to understand consumers’ positions and sentiments related to FOPNL through the posts analysis on social media platform X, ranging from positive to negative. These findings highlight the importance of monitoring not only regulatory compliance but also public attitudes toward health policies, as a strategy to inform policy refinement, strengthen public trust, and enhance the impact of nutrition labeling initiatives.